Different expression patterns of inflammatory cytokines induced by lipopolysaccharides from Escherichia coli or Porphyromonas gingivalis in human dental pulp stem cells - Chunhua Lan; Shuai Chen; Shan Jiang; Huaxiang Lei; Zhiyu Cai; Xiaojing Huang (BMC, 2022)
Abstract Background Lipopolysaccharide (LPS) is one of the leading causes of pulpitis. The differences in establishing an in vitro pulpitis model by using different lipopolysaccharides (LPSs) are unknown. This study aimed to determine the discrepancy in the ability to induce the expression of inflammatory cytokines and the underlying mechanism between Escherichia coli (E. coli) and Porphyromonas gingivalis (P. gingivalis) LPSs in human dental pulp stem cells (hDPSCs). Material and methods Quantitative real-time polymerase chain reaction (QRT-PCR) was used to evaluate the mRNA levels of inflammatory cytokines including IL-6, IL-8, COX-2, IL-1β, and TNF-α expressed by hDPSCs at each time point. ELISA was used to assess the interleukin-6 (IL-6) protein level. The role of toll-like receptors (TLR)2 and TLR4 in the inflammatory response in hDPSCs initiated by LPSs was assessed by QRT-PCR and flow cytometry. Results The E. coli LPS significantly enhanced the mRNA expression of inflammatory cytokines and the production of the IL-6 protein (p < 0.05) in hDPSCs. The peaks of all observed inflammation mediators' expression in hDPSCs were reached 3-12 h after stimulation by 1 μg/mL E. coli LPS. E. coli LPS enhanced the TLR4 expression (p < 0.05) but not TLR2 in hDPSCs, whereas P. gingivalis LPS did not affect TLR2 or TLR4 expression in hDPSCs. The TLR4 inhibitor pretreatment significantly inhibited the gene expression of inflammatory cytokines upregulated by E. coli LPS (p < 0.05). Conclusion Under the condition of this study, E. coli LPS but not P. gingivalis LPS is effective in promoting the expression of inflammatory cytokines by hDPSCs. E. coli LPS increases the TLR4 expression in hDPSCs. P. gingivalis LPS has no effect on TLR2 or TLR4 expression in hDPSCs.